Service Quality and the Mediating Effect of Corporate Image on the Relationship between Customer Satisfaction and Customer Loyalty in the Malaysian Hotel Industry - Boon-Liat Cheng (Gadjah Mada International Journal of Business, 2014)
Service quality is vital to the success of  any service organization. The rapid growth of the Malaysian hotel industry in the 2000’s forced hotel operators to seriously recognize the importance of service improvement in order to gain competitive advantage. This study aims to examine the impact of service quality on customer satisfaction, and how customer satisfaction subsequently affects customer loyalty in the hotel industry in Malaysia. This study also investigates the mediating effect of corporate image  on the  relationship between customer satisfaction and customer loyalty.  A systematic  sampling approach was adopted  to collect data through self-administered questionnaires from 500 hotel guests. Preliminary data analysis, descriptive analysis, reliability test and regression analysis were adopted to ana-lyze  the  reliability  of  items and the  hypothesized  relationships  in the  proposed  research model.  The findings revealed that perception of service quality is significantly related to customer satisfaction, which in turn generates positive customer loyalty in the hotel industry. Besides, corporate image is found to be a partial mediator in the relationship between customer satisfaction and customer loyalty. Overall, the find-ings of this study would help hotel operators to formulate and implement effective marketing manage-ment strategies to cope with the keen competition in the hotel service industry.